What Is the Effect of Health Coaching Delivered by Physical Therapists? A Systematic Review of Randomized Controlled Trials. Issue 10 (16th July 2019) - Rethorn, Zachary D; Pettitt, Cherie D
Abstract: Background: Health coaching has emerged as an intervention for improving health behaviors. Given the recent increased integration of health coaching into physical therapist practice, there has been a subsequent rise in research examining the effects of health coaching provided by physical therapists. However, there is a lack of literature summarizing the effectiveness of health coaching delivered by physical therapists in changing patient health behaviors. Purpose: The purpose of this study was to systematically review the effects of health coaching delivered by physical therapists on promoting participant health behaviors. Data Sources: Cochrane, CINAHL, MEDLINE, PEDro, PsycINFO, and Web of Science databases were searched from inception to May 26, 2018, to identify randomized controlled trials examining the effects of health coaching delivered by physical therapists. Study Selection: Two reviewers independently screened titles, abstracts, and full texts according to inclusion and exclusion criteria to determine study eligibility. Data Extraction: Methodological quality was assessed using Physiotherapy Evidence Database (PEDro) scores. Risk of bias was assessed using the Cochrane Collaboration risk-of-bias assessment tool. Data were extracted using a standardized data extraction form describing study methods, design, and outcomes. Data Synthesis: Eleven trials met the inclusion criteria for this study. Health coaching produced positive effects on physical activity (6 studies) as well as physiological and psychological secondary outcomes. Limitations: The inclusion of only 11 randomized controlled trials in this review could limit the generalizability of the findings. The heterogeneity of the findings precluded the performance of a meta-analysis. Conclusions: Research on the effectiveness of health coaching delivered by physical therapists on health behavior outcomes is mixed. Data indicate statistically significant changes in some health behavior, physiological, and psychological outcomes.